Compact model with physical parameter prediction capability for RF amplifiers - Rafael-Valdivia, Guillermo (Universidad Pedagógica y Tecnológica de Colombia, 2019)
In this work presents an analysis of field effect transistors using pulsed voltage sources has been presented. Microwave measurements have been made in HEMT's and LDMOS technology devices highlighting the difference between the static and dynamic behavior of these devices. Based on measurements, data processing has been performed, deriving a new equation with the ability to reproduce both types of behavior with high precision and at different points of operation. Consequently, the work provides a new model based on a non-linear four-terminal circuit. The relevance of this model is the ability to predict physical effects such as frequency dispersion and electronic mobility of the semiconductor device. This is important because the frequency dispersion is one of the most important problems of modern communication systems that generates memory effects limiting the ability to transmit signals of high bandwidth. The fact of being able to predict the electronic mobility and the frequency dispersion help the circuit designer to improve their quality and design time. It also allows the RF component manufacturing industry to save production costs as this technique allows to predict the behavior of the circuits before implementing them. The presented methodology has been validated through the implementation of a power amplifier in LDMOS technology using the proposed technique. The proposed model is open since the proposed new technique can be implemented in any of the conventional models currently used in the industrial and academic field.